Keadilan Distribusi Infak Ekonomi dan Dampaknya terhadap Akses Modal Usaha Mikro - Raodatul Jannah (Jujurnal Publisher, 2025)
This study addresses the problem of whether the distributional justice of economic charity (infak) is able to influence microenterprise access to finance. The objective is to analyze the conceptual linkage between fairness in infak distribution and the resulting ability of microenterprises to obtain and utilize financial capital productively. Using a qualitative library-research approach, the study synthesizes primary conceptual insights from relevant literature and supporting secondary sources drawn from books, journals, and scientific reports based on the key themes of distributional justice, economic charity, and microenterprise access to finance. The data are analyzed through content analysis to identify recurring patterns and relationships among these concepts. The study concludes that when infak distribution is proportional, appropriately targeted, and consistent, it is more likely to support microenterprises through modal-related needs, thereby improving access to finance as a multidimensional outcome.